Formal Constitutionality Review of Legislation at the Constitutional Court: Case of the Nusantara Capital City Law (IKN Law) - Afkar, Kardiansyah; Zainal Arifin Mochtar (As-Siyasi: Journal of Constitutional Law, 2025)
The IKN law has faced criticism due to its legislative process being deemed formally flawed, particularly in terms of transparency, public participation, and accountability. These shortcomings raise constitutional concerns and question the legitimacy of the legislative process behind a law that will significantly shape Indonesia’s future governance. This study aims to analyze the objective parameters in the formal-constitutionality review of laws in the Constitutional Court, explicitly focusing on Law Number 3 of 2022 concerning the Nusantara capital city. The research employs a normative-analytical method using a statutory and analytical approach based on secondary data, such as relevant legislation, legislative deliberation records, and expert opinions. The findings reveal that the legislative process of the IKN law did not fully comply with the principles of good regulatory practice, particularly in terms of openness and public involvement. The accelerated process created gaps in transparency and accountability, potentially resulting in constitutional harm to society. Additionally, the IKN law includes several delegations of regulatory authority to implementing rules, increasing the risk of abuse in the legislative process. This study concludes by emphasizing the significance of formal review in upholding the rule of law and ensuring that enacted laws reflect constitutional values and serve the public interest. It also contributes to developing a more objective and accountable legislative evaluation framework in Indonesia